1980
DOI: 10.1111/j.1432-1033.1980.tb04899.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Cibacron Blue F3GA to the Flavin and NADH Sites in Cytochrome b5 Reductase

Abstract: The behaviour of cytochrome hs reductase holoenzyme and apoenzyme toward blue-dextranSepharose has been studied. Holoenzyme was adsorbed at low ionic strength and could be eluted with 100 pM NADH or NAD'. Flavin-free enzyme was even more strongly bound and could be eluted with 1 M NaCl, or 100 pM NADH + 10 pM FAD. Separately the cofactors were without effect.FMN was less effective than FAD. ADP and AMP eluted nothing.Cibacron blue F3GA was found to exert a mixed inhibition on NADH oxidation. Dye binding to hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
2

Year Published

1982
1982
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 47 publications
4
35
2
Order By: Relevance
“…Furthermore, the measured k,,, for the reverse reaction found in this work is 3.6 s -I ; this low rate cannot be due to slow bromolactate dissociation, for the following reason. The kinetic parameters K , and k,,, determined for bromolactate are not very different from those of lactate (see below and Table2); we can then reasonably assume that the two hydroxy acids will bind and dissociate at rates of a similar order of magnitude; in particular, the value of k,,, for lactate was calculated to lie within 50-100 s-' [23]. This reasoning indicated that under our experi- mental conditions oxidized flavin is reduced much more rapidly than it is produced.…”
Section: Oxidation State Of the Heme During Turnovermentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the measured k,,, for the reverse reaction found in this work is 3.6 s -I ; this low rate cannot be due to slow bromolactate dissociation, for the following reason. The kinetic parameters K , and k,,, determined for bromolactate are not very different from those of lactate (see below and Table2); we can then reasonably assume that the two hydroxy acids will bind and dissociate at rates of a similar order of magnitude; in particular, the value of k,,, for lactate was calculated to lie within 50-100 s-' [23]. This reasoning indicated that under our experi- mental conditions oxidized flavin is reduced much more rapidly than it is produced.…”
Section: Oxidation State Of the Heme During Turnovermentioning
confidence: 99%
“…It has been shown that in the tetramer there are privileged heme-flavin pairs, between which electron transfer is rapid [22, Electron transfer between any member of one pair to any member of another pair is supposed to be slow, with rates lower than 10 s-' [23]. The rate constant for lactate to flavin transfer, which is the slow step in the forward reaction, was estimated by simulation studies to be 120 s-' at 24 "C [20,22].…”
Section: Oxidation State Of the Heme During Turnovermentioning
confidence: 99%
See 1 more Smart Citation
“…In order to remove contaminating hemoglobin, an additional step was added to the purification, namely chromatography on blue-dextran-Sepharose [15]. For flavin removal, 15 pM reductase in 10 mM Tris/HCl buffer, 1 mM EDTA, 0.1 dithiothreitol, pH 8.5, was brought to pH 2.3 by rapid mixing with 0.8 M HCl at 0°C. The solution was stirred for a few seconds with HCI-washed charcoal and finally centrifuged for a few minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Before use it was equilibrated against the required buffer by dialysis or filtration on Sephadex G-25. NADH cytochrome b5 reductase was solubilized by proteolysis from beef liver microsomes according to Takesue and Omura [14]. In order to remove contaminating hemoglobin, an additional step was added to the purification, namely chromatography on blue-dextran-Sepharose [15]. For flavin removal, 15 pM reductase in 10 mM Tris/HCl buffer, 1 mM EDTA, 0.1 dithiothreitol, pH 8.5, was brought to pH 2.3 by rapid mixing with 0.8 M HCl at 0°C.…”
Section: Methodsmentioning
confidence: 99%